2020
DOI: 10.31557/apjcp.2020.21.5.1415
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Breast Cancer among Female Students and Faculty from Najran University, Najran, Saudi Arabia

Abstract: The clinical stage of BC at the time of presentation is regarded as one of the most substantial prognostic factors of survival (Siegel et al., 2019). The five-year overall survival rates for patients with localized and regional diseases are very favorable, and may reach up to 99% and 85%, respectively (Siegel et al., 2019). Conversely, the five-year overall survival rate for patients with metastatic disease is very dismal, and may drop

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
4
19
0
1
Order By: Relevance
“…Students have knowledge about BC from different sources, the most common sources being university studies, the Internet, and social media. This finding is consistent with studies conducted in Egypt, Ethiopia, and Saudi Arabia universities that revealed the majority of medical students became aware of BC by their syllabuses [ 19 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Students have knowledge about BC from different sources, the most common sources being university studies, the Internet, and social media. This finding is consistent with studies conducted in Egypt, Ethiopia, and Saudi Arabia universities that revealed the majority of medical students became aware of BC by their syllabuses [ 19 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…The maximum achievable score was 24, and a higher score represented a higher level of knowledge. The cut-offs were defined as poor knowledge (0-7), low knowledge (8)(9)(10)(11)(12)(13), adequate knowledge (14)(15)(16)(17)(18), and excellent knowledge (19)(20)(21)(22)(23)(24). We considered poor and low knowledge as an unacceptable level and adequate and excellent knowledge as an acceptable level.…”
Section: Research Instrument and Translationmentioning
confidence: 99%
“…However, those studies did not differentiate among health and non-health college students and did not use a validated research instrument to document knowledge. In a study conducted in Najran, it was reported that students and faculty had a better general knowledge of BC, but poor knowledge about its symptoms (13). In addition, there is a plethora of evidence that highlights these issues among the general Saudi public as well.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted to assess the awareness, knowledge, attitudes and perceptions of female students and staff at a university in the Hail region in Saudi Arabia. The results of this study indicate that educational campaigns were the main source of information about breast cancer (54.1%) compared to 43% from a study conducted at Najran University [11]. This was mainly due to their participation in these campaigns, which are organized annually to improve the public's awareness of breast cancer through lectures, conferences, videos and other source materials.…”
Section: Discussionmentioning
confidence: 77%